AN EVOCATION OF ION VIDU 150 YEARS AFTER HIS BIRTH. HIS ACTIVITY AS A COMPOSER AND A CONDUCTOR - Ion-Alexandru ARDEREANU (Studia Universitatis Babeş-Bolyai. Musica)
Towards the end of the year 2013 the birth of the composer Ion Vidu will be marked by the commemoration of the 150 years that have passed. A memorable figure of the musical scene from Banat, the founder and promoter of the Orthodox choral movement for which Banat is known even internationally, Ion Vidu can righteously be defined as a most complex cultural personality whose legacy entitles him to be called a canonical composer for the history of the Romanian choral music and a remarkable conductor, teacher, publicist and organizer of the cultural life in Banat in general and of the choral movement in the same area in particular. Thus, in this commemorative year, this paper sets out to highlight yet again not a general portrait of Ion Vidu (in which case the risk of a shallow approach would be very high), but the two most common dimensions of his personality: Ion Vidu, the composer and the conductor.